Nursing care to the patient with implantable automatic fibre-removing machine - Sandra Isabel García Mora (Fundación para el Desarrollo de la Enfermería, 2011)
The primary prevention of the cardiac sudden death constitutes one of the main challenges of the present cardiology. The main reason for this interest comes dice by the little possibilities of surviving an extra-hospital cardiac shutdown, smaller of 20%.El implantable automatic fibre-removing machine (DAI) is the most effective therapy to prevent the cardiac sudden death related to ventricular tachyarrhythmias. From the beginnings of the therapy by means of the DAI, besides the survival and the quality of life of the patients it has constituted an important reason for attention. The carrying patients present/display agreements that can have an excellent impact in their quality of life. The infirmary personnel must know the therapy the DAI, to be able to provide to the patients and their familiar surroundings the optimal cares to confront its daily life, a level of confidence and comfort derived from the positioning of a permanent electronics.